Crystal Structure and Optical Property of Perovskite FAPbBr3 Single Crystals Synthesized by using Anti-Solvent Assisted Vapor Crystallization Method - Sugandi, Adinda Sugandi Apriliani Nur; Bahtiar, Ayi (Universitas Padjadjaran, 2025)
Perovskite formamidinium lead tribromide or FAPbBr3 single crystal has been intensively developed as a material for γ-ray detectors, which are very necessary in medical diagnostics in Positron Emission Tomography (PET) radio nuclear devices, in order to obtain high resolution and contrast images to accurately diagnose patient illnesses. This is because FAPbBr3 has high Z, low defect density, high mobility-lifetime (µ−τ) product, is stable against γ-ray exposure, and can be synthesized in the form of large-dimensional single crystals and low-cost films. In this work, FAPbBr3 single crystals were synthesized using the AVC (Anti-solvent assisted Vapor Crystallization) method. The FAPbBr3 crystal has dimension of 5 mm x 5 mm x 3 mm, a single cubic crystal structure and a gap energy of 2.10 eV. The XPS results show that all bonds originating from the constituent elements of the FAPbBr3 crystal are clearly observed. However, a single peak originating from O1s at 531.10 eV is clearly observed, indicating that the FAPbBr3 had undergone oxidation. Optimization of the synthesis methos is needed to prevent oxygen penetration into the crystal.